1987
DOI: 10.1002/j.1460-2075.1987.tb02714.x
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNAs of a strongly-expressed late gene of cowpox virus contain 5′-terminal poly(A) sequences.

Abstract: We have identified and characterized one of the most strongly‐expressed genes of cowpox virus (CPV). This is the gene encoding the major protein component of the A‐type inclusion bodies produced by this virus. This gene (designated the 160K gene) is transcribed late during the infection. Analyses of its mRNAs showed that these late RNAs, unlike all other characterized late mRNAs of poxviruses, are uniform in length. However, the most remarkable feature of the mRNAs of the 160K gene is the structure of their 5′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 61 publications
6
76
0
Order By: Relevance
“…However, a more direct analysis is required to confirm a decapping preference. VACV intermediate and late transcripts have a unique 5Ј poly(A) leader, further differentiating them from host and VACV early transcripts (5,30,31). It is known that decapping of cellular mRNAs depends on shortening of the 3Ј poly(A) tail and dissociation of the poly(A) binding protein, although the mechanism is not completely understood (26,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, a more direct analysis is required to confirm a decapping preference. VACV intermediate and late transcripts have a unique 5Ј poly(A) leader, further differentiating them from host and VACV early transcripts (5,30,31). It is known that decapping of cellular mRNAs depends on shortening of the 3Ј poly(A) tail and dissociation of the poly(A) binding protein, although the mechanism is not completely understood (26,32).…”
Section: Discussionmentioning
confidence: 99%
“…plement of the three As within the motif {i.e., the three Ts on the template strandl has been proposed to be the pseudo-template for synthesis of a poly(A) head, which immediately follows the capped 5' end of the late transcripts (Bertholet et al 1986, 198L Patel andPickup 1987;Schwer et al 1987;Schwer and Stunnenberg 19881. Results from various in vitro systems Stunnenberg 1988~ Wright andMoss 1989} support the pseudo-templated polymerization hypothesis for the poly{A) head. Remarkably, the length of the poly(A) head, -3 5 As, is rather constant both in vitro and in vivo.…”
Section: T T C a T ( '~T T ' -" G G T T T T T C A A A Amentioning
confidence: 99%
“…It has been suggested that the occlusion of mature virions into ATIBs allows prolonged survival and more efficient dissemination of the virions (Ichihashi et al, 1971). CoP virus-specific ATIBs appear late in the viral multiplication cycle, and the 160K A-type inclusion protein (ATIP) (Shida et al, 1977) is a late viral gene product (Patel & Pickup, 1987; The nucleotide sequence data reported in this paper have been submitted to the EMBL database and assigned accession number X69774. Funahashi et al, 1988) accumulating in high amounts in infected cells (Patel et al, 1986).…”
mentioning
confidence: 99%